Tracing the Roots of Utilitarianism and Rationality in Social Exchange Theory to Develop a Sustainable Organizational Behavior Model - Teguh Setiawan Wibowo; Ratih Dewi Titisari Haryana (LPPM STIE YAPAN, 2026)
This study traces the philosophical roots of utilitarianism and rationality in Social Exchange Theory (SET) and reconceptualizes it to develop a sustainable organizational behavior model in human resource management. Employing a library research approach with theoretical analysis of Scopus and Web of Science-indexed literature, the findings reveal that SET has been treated as self-contained, whereas historically and philosophically it derives from utilitarianism (Bentham, Mill), behaviorism (Skinner), and rational choice theory (Coleman). The reduction of utilitarianism's complexity, particularly Mill's concept of higher pleasures and the conceptual ambiguity between Homans' and Blau's approaches have led to limitations in explaining sustainable organizational behavior. This study reconceptualizes SET through a three-level model integrating philosophical level (utilitarianism, capability approach), theoretical level (SET, self-determination theory, social identity theory), and practical level (green HRM, work-life balance, employee well-being). This model shifts focus from managing transactions to cultivating relationships, recognizing the roles of value congruence, basic psychological need fulfillment, and generalized reciprocity in fostering sustainable behavior. The study concludes that SET needs reconceptualization as a theory of co-creation of value transcending individual utility maximization, while identifying future research agendas for developing more humanistic and relevant HRM scholarship in response to sustainability demands.